Cultural variation impacts paternal and maternal genetic lineages of the Hmong-Mien and Sino-Tibetan groups from Thailand - Wibhu Kutanan (2020)
© 2020, The Author(s). The Hmong-Mien (HM) and Sino-Tibetan (ST) speaking groups are known as hill tribes in Thailand; they were the subject of the first studies to show an impact of patrilocality vs. matrilocality on patterns of mitochondrial (mt) DNA vs. male-specific portion of the Y chromosome (MSY) variation. However, HM and ST groups have not been studied in as much detail as other Thai groups; here we report and analyze 234 partial MSY sequences (∼2.3 mB) and 416 complete mtDNA sequences from 14 populations that, when combined with our previous published data, provides the largest dataset yet for the hill tribes. We find a striking difference between Hmong and IuMien (Mien-speaking) groups: the Hmong are genetically different from both the IuMien and all other Thai groups, whereas the IuMien are genetically more similar to other linguistic groups than to the Hmong. In general, we find less of an impact of patrilocality vs. matrilocality on patterns of mtDNA vs. MSY variation than previous studies. However, there is a dramatic difference in the frequency of MSY and mtDNA lineages of Northeast Asian (NEA) origin vs. Southeast Asian (SEA) origin in HM vs. ST groups: HM groups have high frequencies of NEA MSY lineages but lower frequencies of NEA mtDNA lineages, while ST groups show the opposite. A potential explanation is that the ancestors of Thai HM groups were patrilocal, while the ancestors of Thai ST groups were matrilocal. Overall, these results attest to the impact of cultural practices on patterns of mtDNA vs. MSY variation.